Re-Paying Attention to Visitor Behavior: A Re-Analysis using Meta-Analytic Techniques. (20th June 2016) - Castro, Yone; Botella, Juan; Asensio, Mikel
Abstract: The present study describes a meta-analytic review of museum visitors' behavior. Although there is a large number of visitor studies available, their cumulative importance has not been determined due to the lack of rigorous methods to determine common causes of visitors' behaviors. We analyzed Serrell's (1998 ) database of 110 studies, defining a number of variables that measure visitors' behaviors in exhibition spaces which exceeded the most typical and obvious ones. We defined four indexes of effect size and obtained their combined estimates: average time per feature [ATF● = 0.43 (0.49; 0.37)], percentage of diligent visitors [dv● = 30% (0.39; 0.23)], inverse of velocity [Iv● = 4.07 min/100m2 (4.55; 3.59)], and stops per feature [SF● = 0.35 (0.38; 0.33)], and we analyzed the role of relevant moderating variables. Key findings indicate, for example, that the visiting time for each display element relates to the size of the exhibition and its newness, and visitor walking speed is higher in large exhibit areas. The indexes obtained in this study can be understood as references to be used for comparison with new evaluations. They may help to predict people's behavior and appreciation of new exhibitions, identifying important problems in museum designs, and providing new research tools for this field.